An MEG study of alpha modulation in patients with schizophrenia and in subjects at high risk of developing psychosis. - Koh Y; Shin KS; Kim JS; Choi JS; Kang DH; Jang JH; Cho KH; O'Donnell BF; Chung CK; Kwon JS; Koh, Yuri; Shin, Kyung Soon; et al. (Schizophrenia Research, 2011)
Background: Selective attention involves a dynamic interaction between attentional control systems and brain oscillations. In auditory processing, selective attention toward task-relevant stimuli and the inhibition of irrelevant information can be considered as aspects of top-down attentional control. Oscillatory rhythms in the alpha band have been found to play an important role during top-down processing. Because attention deficits have been noted in patients with schizophrenia, we examined alpha oscillations in schizophrenia and in the prodromal phase of psychosis.Methods: The present study compared alpha oscillations using measures of both spectral power and inter-trial coherence in 17 subjects at ultra-high-risk, 10 patients with schizophrenia, and 18 matched normal control subjects. Whole-head magnetoencephalography (MEG) was conducted during an auditory oddball task to investigate alpha brain activity related to selective attention to target stimuli and selective inhibition of irrelevant stimuli.Results: Patients with schizophrenia showed diminished alpha event-related desynchronization compared with the control subjects, while the ultra-high-risk subjects had values intermediate between the control subjects and schizophrenia patients. Similarly, alpha inter-trial phase coherence was lower in the schizophrenia patients than the ultra-high-risk subjects, and lower in the ultra-high-risk subjects than the normal control subjects. Furthermore, alpha band activity in the parieto-occipital region was more severely depressed in the schizophrenia patients than the ultra-high-risk subjects.Conclusions: The altered alpha band activity in the ultra-high-risk group indicates that a deficit in top-down attentional control exists before the onset of psychosis. The alpha event-related desynchronization and inter-trial coherence may reflect a functional decline in the prodromal phase of schizophrenia.